Food safety in Vietnam: where we are at and what we can learn from international experiences. Issue 1 (December 2017) - Nguyen-Viet, Hung; Tuyet-Hanh, Tran; Unger, Fred; Dang-Xuan, Sinh; Grace, Delia
Abstract Food-borne diseases are attracting a lot of attention in Vietnam as a result of repeated episodes of adulterated and unsafe food. In this paper, we provide some perspectives on food safety in Vietnam from the point of view of an international research institution working on food safety with partners in the country. We argue that one of the key issues of food safety in Vietnam is that certain food value chain stakeholders lack ethics, which leads to the production and trading of unsafe foods in order to make profits irrespective of adverse health effects on consumers. In turn, the shortfall in ethical behaviours around food can be attributed to a lack of incentives or motivating factors. Although food safety causes panic in the population, it is unclear how much contaminated food contributes to the burden of food-borne diseases and food poisonings in Vietnam. However, globally, the biggest health problem associated with food are infections from consuming food contaminated with viruses, bacteria or parasites. A major food safety challenge is the inappropriate way of communicating food risks to the public. Another key constraint is the inherent difficulty in managing food in wet markets and from smallholder production. On the other hand, local foods, and local food production and processing are an important cultural asset as well as being essential to food safety, and these aspects can be put at risk if food safety concerns motivate consumers to purchase more imported foods. In this paper, we also discuss good experiences in food safety management from other countries and draw lessons learnt for Vietnam on how to better deal with the current food safety situation.